Phaleria Macrocarpa and Averrhoa Bilimbi L as Alternative Medicines in the Treatment of Patients with Diabetes Mellitus Type 2 - Laila Sholehah; Shanti Listyawati; Arief Nurudhin (Jurnal Keperawatan, 2022)
DM is a metabolic disease characterized by blood glucose levels that closely related to oxidative stress and lipid abnormalities. There are side effects of the drugs, such as nausea, dizziness, and so other alternatives are needed with natural ingredients and lower side effects. One of them are Phaleria macrocarpa and Averrhoa bilimbi. The compounds can reduce GDP,MDA and improve lipid profile in DMT2. The aim is to determine Phaleria macrocarpa and Averrhoa bilimbi as alternative treatments. The method is a systematic review of 34 journals. Based on the analysis, Phaleria macrocarpa and Averrhoa bilimbi were shown to reduce GDP,MDA and improve lipid profile. The decrease GDP from saponin can reduce glucose absorption in the intestine and inhibit the glucose transporter GLUT-1, while the decrease MDA is due to flavonoids which play a role in suppressing free radicals production, inhibiting the production of inflammatory mediators, and increasing endogenous antioxidants. Improvement of lipid profile from niacin can reduce blood cholesterol levels by inhibiting VLDL secretion mechanism. It was concluded that Phaleria macrocarpa and Averrhoa bilimbi could be used as alternative drugs for the treatment of DMT2 by lowering GDP, MDA and improving lipid profile.